1989
DOI: 10.1136/oem.46.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Urinary t,t-muconic acid as an indicator of exposure to benzene.

Abstract: A method for rapidly determining t,t-muconic acid (MA) by high performance liquid chromatography was developed and successfully applied to urine samples from 152 workers exposed to benzene (64 men, 88 women) and 213 non-exposed controls (113 men, 100 women). The MA concentrations in urine correlated linearly with time weighted average benzene concentrations in the breath zone air of workers. A cross sectional balance study showed that about 2% of benzene inhaled is excreted into the urine as MA. The MA concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
5

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 16 publications
1
47
0
5
Order By: Relevance
“…Thus, the present survey not only supports the opinion that PMA is a good biomarker of benzene exposure 8,9,[15][16][17][18][19] , but has demonstrated that PMA is useful even under the condition of co-exposure to other aromatics and most probably to other solvents in general. The latter observation suggests that, as a benzene exposure marker, PMA is superior to mono-to tri-hydroxylated benzenes [phenol 27) , quinol 27) and catechol 27) , 1,2,4-benzenetriol 11) ] and t,t-muconic acid 13) , because the excretion of these urinary benzene metabolites other than PMA are all known to be suppressed by coexposure to other aromatics. For example, urinary excretion of phenolic metabolites were suppressed by 33 to 60% 11) , and it was as large as 74% in case of t,t-muconic acid 13) , when metabolite excretion of by workers exposed to benzene and toluene together was compared with the excretion of those exposed to benzene only.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, the present survey not only supports the opinion that PMA is a good biomarker of benzene exposure 8,9,[15][16][17][18][19] , but has demonstrated that PMA is useful even under the condition of co-exposure to other aromatics and most probably to other solvents in general. The latter observation suggests that, as a benzene exposure marker, PMA is superior to mono-to tri-hydroxylated benzenes [phenol 27) , quinol 27) and catechol 27) , 1,2,4-benzenetriol 11) ] and t,t-muconic acid 13) , because the excretion of these urinary benzene metabolites other than PMA are all known to be suppressed by coexposure to other aromatics. For example, urinary excretion of phenolic metabolites were suppressed by 33 to 60% 11) , and it was as large as 74% in case of t,t-muconic acid 13) , when metabolite excretion of by workers exposed to benzene and toluene together was compared with the excretion of those exposed to benzene only.…”
Section: Discussionmentioning
confidence: 95%
“…Benzene exposure in cokeries in the iron and steel industry is also known 8,9) . This study group has been studying on urinary biomarkers of occupational exposure to benzene such as catechol 10) , quinol 10) , 1,2,4-benzenetriol 11,12) as well as t,t-muconic acid 13) in addition to a traditional marker of phenol 14) . Urinary phenylmercapturic acid (PMA; N-acetyl-S-phenyl-L-cysteine), a N-acetylcysteine conjugate of benzene, has also been evaluated as a marker of exposure to low-level benzene 8,9,[15][16][17][18][19][20] , but the analytical methods employed are rather complex, e.g., requiring derivatization or clean-up through columns before instrumental analysis [21][22][23][24][25] such as gas chromatography-mass spectrometry 15) or liquid chromatography-mass spectrometry 26) , and application of the methods to routine occupational health services appear to be not practical.…”
Section: Introductionmentioning
confidence: 99%
“…Methods based on its urinary metabolites, such as phenol and the newly proposed trans, trans-muconic acid (4,5), are nonspecific because these compounds are also generated from sources other than benzene. S-phenylmercapturi c acid in urine is reported to be useful in monitoring exposures even below benzene concentrations of I cm 3 • m-3 (6).…”
mentioning
confidence: 99%
“…Além do hábito de fumar 80 e a ingestão de ácido sórbico 51,52 , a co-exposição ao tolueno também interfere na avaliação da exposição ao benzeno 60,81,82 . Há suspeitas que hidrocarbonetos policíclicos aromáticos (HPAs) também interfiram nesta avaliação 56 .…”
Section: áCido Transtrans-mucônicounclassified